2011
DOI: 10.1007/s00464-011-2096-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term results between laparoscopy-assisted gastrectomy and open gastrectomy with D2 lymph node dissection for advanced gastric cancer

Abstract: The findings show that LAG with D2 lymph node dissection is acceptable in terms of long-term results for advanced gastric cancer cases and may be applicable for advanced gastric cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 33 publications
2
60
0
Order By: Relevance
“…A small number of investigators reported that laparoscopic gastrectomy was oncologically a safe procedure for AGC with long-term outcomes similar to those for open surgery [29,30]. This study also showed that the laparoscopic procedure did not increase peritoneal recurrence.…”
Section: Discussionmentioning
confidence: 51%
“…A small number of investigators reported that laparoscopic gastrectomy was oncologically a safe procedure for AGC with long-term outcomes similar to those for open surgery [29,30]. This study also showed that the laparoscopic procedure did not increase peritoneal recurrence.…”
Section: Discussionmentioning
confidence: 51%
“…Some authors have reported that LADG also has short-term benefits and oncological safety for advanced gastric cancer [2]. The technical feasibility and oncological safety of LTG have also been recently reported.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, because LADG is considered technically feasible and oncologically safe for the treatment of early gastric cancer, its indications have been extended from early gastric cancer to advanced disease [2]. Because the indication for LADG has expanded, surgeons who have experience with LADG cautiously attempt laparoscopic total gastrectomy (LTG) in selected patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant differences in hospital mortality. DFS in LTG was similar to that in OTG (HR, 0.62; 95% CI, 0.30, 1.27; P= 0.191) (Fig.2-3) [1][2][3][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 71%